‘There’s no waiting list, just press play’: listeners' experiences of mental-health-related podcasts - Naoise O Caoilte; Sharon Lambert; Raegan Murphy (James Cook University, 2024)
Introduction: The activity of podcasting has increased exponentially but little is known about the qualitative listener experiences of podcasts related to mental health. The aim of this study was to understand what listeners of mental health podcasts obtain from this medium. Participants were asked questions relating to mental health literacy, stigma and help-seeking behaviour. Methods: The study gathered data, via an online survey (n=722). This article reports on the responses to open-ended questions: 'What do you take away from listening to mental health-related podcasts? What do you learn about yourself (or a loved one)? What do you find most useful about listening to mental health-related podcasts?' Inductive thematic analysis was utilised. Results: Thematic analysis produced five core themes: accessibility, mental health literacy, potential pitfalls, reassurance and lived experiences. Accessibility of material and discussions featuring professionals and people with lived experience were reported key highlights. Conclusion: Results indicate that podcasts influence the development of mental health literacy, reduce stigma and increase help-seeking. Given the challenges with service access in underserved populations, there is a potential role for the use of podcasts in rural regions.